MATERNAL HEALTHCARE SEEKING BEHAVIOUR IN RURAL COMMUNITIES OF IDO-OSI LGA, EKITI STATE, NIGERIA (Annals of the University of Bucharest. Geography Series, 2024)
This study assessed rural women’s behaviour towards Antenatal and Postnatal Care in Ido-Osi Local Government  Area of Ekiti State, Nigeria. It identified the type of healthproblems confronting them; examined their choice of healthcare; determined the factors influencing such choices and assessed factors associated with ANC and PNC serviceutilization. Primary data were generated through questionnaire administration among 399 respondents in three communities in a systematic way. Secondary data were obtained from Ido-osi LGA, textbooks and internet. Frequency-tables, percentages and ranking were employed to analyze the data. Findings revealed that 84% are married, 94% between 21 and 50years, 89.7% are gainfully employed and 81.4% earn less than N100,000/month. Vomiting is a common illness among pregnant women while dizziness is the sickness among those that gave birth in the last two years. Most of the sampled women consult female traditional birth attendance (92.2%), private health facility (89.7%) and government health facilities (83%).Reduced cost and proximity are the main determinants of caregiver. Socio-economic and Knowledge of pregnancy complications are the most significant factors that influence ANC and PNC service utilization respectively. The study recommends educating the rural women on the importance of modern health services before, during after child birth.
Keywords: child birth; child mortality; developing Countries; maternal mortality; pregnancy; rural areas and women